2016
DOI: 10.3390/su8111119
|View full text |Cite
|
Sign up to set email alerts
|

Does Technology Transfer Help Small and Medium Companies? Empirical Evidence from Korea

Abstract: Abstract:We challenge the view that technology transfer from big companies to small and medium (SM) size companies helps SM companies to prosper. With a large dataset of SM companies in Korea, we utilize the stochastic production frontier (SPF) model to examine the productivity of inputs and the generalized linear model (GLM) to compare business performance between two groups of SM companies: SM companies that receive technology transfer and those that do not receive technology transfer from big companies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Firms interact with a myriad of external knowledge sources, such as suppliers, customers, competitors, universities, and research organizations through various forms of collaboration [42]. Research on open innovation distinguishes a firm's openness to external knowledge into external search breadth and depth based on the scope and intensity of interactions with external actors.…”
Section: External Search Activitiesmentioning
confidence: 99%
“…Firms interact with a myriad of external knowledge sources, such as suppliers, customers, competitors, universities, and research organizations through various forms of collaboration [42]. Research on open innovation distinguishes a firm's openness to external knowledge into external search breadth and depth based on the scope and intensity of interactions with external actors.…”
Section: External Search Activitiesmentioning
confidence: 99%
“…Yang et al [10] investigated "the presence of production risk and technical inefficiency for a sample of rice farms in the Xiangyang City of China using a stochastic production frontier framework". Kim et al [11] utilized "the stochastic production frontier model to examine productivity of inputs for small and medium farmers in korea". Bamlaku et al [12] have analyzed "technical efficiency of farmers in three ecological zones in Ethiopia.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…Thus, it is expected that acquiring external knowledge is important for firms to improve innovation and performance. Besides, prior research has demonstrated that firms can improve innovation through external knowledge acquisition [37,38]. External knowledge acquisition (EKA) here is defined as an activity in which firms obtain knowledge from external sources.…”
Section: External Knowledge Acquisition and Mediation Rolementioning
confidence: 99%